Health Related Quality of Life Among COPD Patients a Tertiary Hospital in Bangladesh (East West Medical College Journal, 2026)
Background: Patients with COPD may have significantly reduced health-related quality of life. The most prevalent cause of mortality worldwide, including in Bangladesh, is expected to be COPD. It is caused by long-term exposure to irritating gases or particulate matter, most often from cigarette smoke. People with COPD are at increased risk of developing heart disease, lung cancer and a variety of other conditions. Methods: A descriptive cross-sectional study was conducted among 100 COPD patients who was selected from Shaheed Tajuddin Ahmed Medical College Hospital (STAMCH) Gazipur. Data was collected by using two self-administered questionnaires; including socio-demographic questionnaire and the clinical COPD questionnaire through face to face interview, observation and finding of review literature, thesis compilation, data collection from July 2024 to June 2025. The data was analyzed by using descriptive and inferential statistics. Results: The total number of COPD patients in the study was 100. Their mean age was 61.00± 11.880 years. The patients consisted of 76% men and 24% women. Overall, 70% of patients had low quality of life, and 30% reported high quality of life. This study found that age, gender, level of education, occupation, smoking status, feeling restless, and loss of interest in work were significantly associated with the quality of life among participants. Conclusion: This study revealed that most of the COPD patients had low quality of life.EWMCJ Vol. 14, No. 2, July 2026: 99-105